Description of the males of Euprosthenops australis Simon, 1898 and Euprosthenopsis pulchella (Pocock, 1902) (Araneae: Pisauridae) - Silva, Estevam L. Cruz Da; Sierwald, Petra (Zootaxa, 2014)
The spider family Pisauridae, with 333 described species (Platnick 2014), can be considered as a moderately diverse spider family. Together with the worldwide distribution, its members exhibit an exceptionally wide range of foraging and prey capture behavior, from web-based hunters, water surface hunters to ambush hunters in the vegetation (Silva & Sierwald 2013).